Vibrational Properties of RbInSe2: Raman Scattering Spectroscopy and First-Principle Calculations - Guc, Maxim; Kodalle, Tim; Raghupathy, Ramya Kormath Madam; Mirhosseini, Hossein; Kühne, Thomas D.; Becerril-Romero, Ignacio; Perez-Rodriguez, Alejandro; Kaufmann, Christian A.; Izquierdo-Roca, Victor (Journal of Physical Chemistry C, 2020)
RbInSe2 is attracting growing interest as a secondary semiconductor compound in Cu(In,Ga)Se2-based solar cells by virtue of the recent investigations on absorber post-deposition treatments with alkali metal salts that have resulted in significant efficiency improvements. However, the detection of the RbInSe2 phase on the surface of chalcopyrite absorbers is very challenging due to its nanometric thickness and the limited information available about its fundamental properties. In this context, this work expounds a detailed analysis of the vibrational properties of RbInSe2 that combines first-principle calculations with multiwavelength Raman scattering spectroscopy and provides a methodology for the detection and identification of very thin layers of this material employing solely optical measurements. As a result, here, we present the classification of the different vibrational modes together with the fingerprint Raman spectra of RbInSe2 thin films measured under five different excitations (close to and far from resonance). The employment of a 442 nm excitation wavelength is found to be the most adequate strategy for the detection and characterization of the RbInSe2 phase in view of its resonance with the band gap of the material and its low penetration depth. Additionally, the purity of the deposited thin films as well as the possible influence of the subjacent layers on the Raman spectra of the compound are also investigated by analyzing the presence of secondary phases and by measuring RbInSe2 thin films deposited onto Mo-coated soda-lime glass, respectively. These results set the basis for the future evaluation of the suitability of Raman spectroscopy as a fast and nondestructive characterization technique for the reliable identification and characterization of the nanometric layers of RbInSe2 in Cu(In,Ga)Se2-based solar cells.
CRIS-Team Scopus Importer:2023-03-20